REKOMENDASI SISTEM ALAT GYM PEMBENTUKAN BODY STRUCTURE DAN ASUPAN MAKANAN METODE BACKWARD CHAINING - Yumarlin Yumarlin MZ (Informasi Interaktif, 2018)
Health and fitness are very important for human life, expert systems can provide recommendations and help users to get accurate information without having to directly meet an expert.The purpose of this study is to produce a system to assist users in determining the selection of gym equipment that is appropriate for the purpose of the body structure or body shape to be done and also the intensity of the time the gym equipment users and food intake must be consumed by using the backward chaining method.In the research conducted in the percentage and on average based on the results of the system testing in the gm equipment system recommendation research the body structure formation, of the 5 instructors or trainers as expert systems were assessed for aspects of the user interface showing 52%. Expressing agreement and 60% stated strongly agree to the aspect of software engineering. Keyword:  gym equipment, body structure,backward chaining